Regulatory dispersion modelling in Finland. (4th August 2014) - Kukkonen, J.; Harkonen, J.; Valkonen, E.; Karppinen, A.; Rantakrans, E.
We present a review of regulatory atmospheric dispersion models and their application to environmental impact assessment (EIA) in Finland. The following regulatory models are available: the urban dispersion modeling system, models for dispersion of vehicular pollution, the air pollution information system, and the dispersion model for odorous compounds. All of these models are connected to a meteorological pre–processing model, based on atmospheric boundary–layer scaling. We will also discuss the application of these models in EIA, and the research needs for model development in general.